Towards a Holistic Approach to Sustainable Development: Inner Development as a Missing Link for Sustainability Transformation - Julia Blanc; Annekatrin Meißner (Religions)
The discourse on understanding and implementing sustainable development has so far focused primarily on the external aspects, neglecting the internal dimension of people. The main purpose of our paper is to contribute to addressing this research gap. Therefore, we intend to (1) substantiate existing aspects of the Inner Development Goals (IDGs), (2) complement them, and (3) link the concept of the IDGs to normative discourses in Christian Social Ethics and Social Philosophy. Our results show that the dimensions of Being, Relating, and Collaborating in the IDG Framework can be substantiated by the normative discourse on spirituality and by reference to the social principle of personality in Christian Social Ethics, as well as by the Indian Social Philosophical Perspective of Vimala Thakar which focuses on a value-based approach. This paper suggests that the concept of the IDGs will be strengthened by adding the dimension of Caring—understood as the concern and responsibility for the wholeness in the combining of the inner and outer dimensions. By linking the concept of the Inner Development Goals to the existing normative discourses in Christian Social Ethics and Social Philosophy, our research contributes to making the concept connectable and deepens the discussions on a practical and theoretical level.